Performance as a Proposal for Decolonial Practice in Museums: Three Experiences in Rio de Janeiro (Cadernos de Sociomuseologia, 2025)
This article examines the integration of performance in art museum exhibitions in Rio de Janeiro, highlighting three specific experiences that took place at the Museum of Modern Art in Rio de Janeiro and the Museum of Art of Rio in the years 1965, 2013, and 2023. These experiences provide an in-depth understanding of how performance has challenged the traditional practices of classical art museums since the 1960s, and how it can point towards new forms of engagement and presence in the museum environment, relating to what some authors refer to as decolonial practice or decolonial turn (Quijano, Carvalho Britto). The methodology employed for this article is based on a literature review of decolonial studies and authors in the field of Sociomuseology, as well as interviews with artists. Furthermore, the author attended one of the performances discussed in the article, and a description of the observations made will be used for analysis. The article will examine conceptual and aesthetic elements of performance pieces, as well as their relationship with the museum, museum staff, the audience, and the city as a whole. The aim is to provide a comprehensive perspective that addresses various relevant aspects when considering performance or contemporary dance, i.e., art in motion, as a decolonial practice in museums.Keywords: Sociomuseology; Decolonial; Performance; Contemporary Dance; Museums